Molecular Imprinted Polymers: Useful Tools for Pharmaceutical Analysis - Baggiani, Claudio; Anfossi, Laura; Giovannoli, Cristina (Current Pharmaceutical Analysis, 2006)
Molecular imprinted polymers are man-made materials with predetermined selectivity towards one or more analytes. They have been used as selective stationary phases in several analytical separative techniques. This review discusses the possible uses of imprinted polymers, with a particular emphasis on their use as high pressure and electrochromatographic stationary phases for resolution of optical enantiomers, materials for fast screening of libraries and selective solid-phase extraction for sample clean-up and preconcentration.
Keywords: Chiral separation